Discrimination of the Enantiotopic Faces of Structurally Unbiased Carbenium Ions Employing a Cyclohexadiene‐Based Chiral Hydride Source - Wolff, Benedikt; Qu, Zheng‐Wang; Grimme, Stefan; Oestreich, Martin (Angewandte Chemie International Edition, 2023)
An enantioselective reduction of simple carbenium ions with cyclohexadienes containing a hydridic C−H bond at an asymmetrically substituted carbon atom is disclosed. The net reaction is a transfer hydrogenation of alkenes (styrenes) only employing chiral cyclohexadienes as dihydrogen surrogates. The trityl cation is used to initiate a Brønsted acid‐promoted process, in which a delicate intermolecular capture of a carbenium‐ion intermediate by the aforementioned chiral hydride source is enantioselectivity determining. Exclusively non‐covalent interactions are rendering one of the transition states energetically more favored, giving the reduction products in good enantiomeric ratios. The computed reaction mechanism supports the present findings as well as previous results obtained from studies on other transfer‐hydrogenation methods involving the cyclohexadiene platform. A chiral cyclohexadiene‐based dihydrogen surrogate can distinguish between the enantiotopic faces of benzylic carbenium ions (see Scheme). No covalent interactions are required but instead dispersion controls the facial discrimination as verified by computations.